Impact of storage conditions on the instrumental colour of buckwheat products for meat industry applications - Rakić Radojica; Petričević Maja; Keškić Tanja; Đurović Sanja; Kulić Gordana; Stamenić Tamara; Pisinov Boris (Biotechnology in Animal Husbandry, 2024)
Buckwheat is one of the functional pseudocereals rich in antioxidants, nutrients, bioactive compounds, and phytochemicals. Colour represents one of the most important sensory parameters in the quality assessment of the meat products. The aim of this study was to determine the possible effect of 9-month artificial aging storage at 40 ± 2 °C on the change in instrumental colour of buckwheat products used in the meat industry. In the CIE L*a*b* system, L*, a*, and b* coordinates are used to specify the data of instrumental colour properties. The results were statistically processed by two-way ANOVA (P<0.001) and Tukey's Honestly Significant Difference post-hoc tests (P<0.05). Storage and product type (and their interaction) factors significantly influenced instrumental colour. During storage, significant differences were observed between the time points (0, 3, 6, and 9 months) in flour, with trends of decreasing lightness (L*) and increasing red (a*) and yellow (b*) colour intensity values. Regarding product type, significantly higher L* values were observed in flour, while a* values were higher in grains. Except for the 3rd month, b* values did not show significant differences. The insights gained in this study may indicate the further application of stored buckwheat flour and grains in obtaining technologically justified and colour-sensory acceptable meat end-products for consumers.